A new explanation of Rolling Contact Fatigue in bearing steels based on multiscale models. Issue 1 (1st March 2022) - Sun, Yachao; Cao, Hongrui
Abstract: Rolling Contact Fatigue (RCF) is harmful and inevitable to bearings and usually results in the initiation of subsurface damage. The root cause for this damage is the cumulative plastic deformation accentuated by carbides. This paper gives a new explanation of RCF based on multiscale models. The distribution and change law of subsurface shear stress in bearing steels was previously investigated by a finite element model. A two-phase atomic model of bcc-Fe and cementite was built. Ten alternating shear load cycles were designed to explore the mechanisms of the cyclic plastic accumulation when the atomic model was initially in the elastic, elastic- plastic and plastic stages, respectively. The results show that cyclic softening diversely occurs in all three types of stress responses. Severe cyclic shear deformation eventually leads to earlier cyclic softening and stress yield, which might be the micromechanism of plastic accumulation and RCF in bearing steels.